Efeitos do fogo na assembleia de borboletas na transição Pantanal-Cerrado - Rafaela Aparecida Mariano Fernandes (2023)
fire is one of the main sources of disturbance in several ecosystems, influencing its composition, structure, resource availability and, consequently, the composition of animal communities. Butterflies are sensitive to changes that occur in their habitat and can respond to different fire regimes (frequency and time of occurrence). The objective of this dissertation is to know how butterflies respond to different fire regimes, in relation to the frequency (number of fire events) and time of fire occurrence in the dry season (beginning or end). For this, this dissertation is structured in two chapters, the first being a systematic review and the second an observational study. The first chapter evaluates the existing gaps in ecosystems that were subject to fire events and used butterflies as the object of study and the second chapter evaluates the possible effects of different burning seasons on the butterfly fauna in the Pantanal of Mato Grosso do Sul.